Happiness at Work sebagai Strategi Mengatasi Kelelahan Kerja Pustakawan di Era Digital - Dian Yunihasti (Perpustakaan Universitas Gadjah Mada, 2026)
Digital transformation in library services has expanded librarians’ responsibilities from managing printed collections to handling digital resources, information literacy instruction, and scholarly publication support. These changes increase job demands and may contribute to psychological pressure and burnout among librarians. This study aims to analyze the role of the Happiness at Work concept in addressing librarian burnout in the digital era. The study employed a literature review method using scholarly articles, books, professional reports, and official publications related to burnout and workplace well-being. Data were analyzed descriptively through thematic identification of factors causing burnout and dimensions of Happiness at Work. The findings indicate that librarian burnout is influenced by an imbalance between job demands and available job resources, particularly digital competencies, organizational support, and career development structures. The Happiness at Work concept, which includes positive emotions, engagement, relationships, meaning, and accomplishment, has the potential to improve resilience, motivation, and service quality. Integrating Happiness at Work into library human resource management is essential to reduce burnout and maintain sustainable librarian performance in the digital era.